Analisis Keberlanjutan UMKM: Peran Literasi Keuangan, Digitaliasasi UMKM, dan Keterampilan Akuntansi - Susanto, Barkah; Afafa, Rizal Wahyu; Dewi , Veni Soraya; Yuliani, Nur Laila (ISOQUANT : Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This research aims to empirically test and analyze the influence of financial literacy, digitalization of MSMEs, and accounting skills on the sustainability of MSMEs. The type of research used is quantitative research with the dependent variable used is the sustainability of MSMEs. This research uses quantitative methods. The sample in this study used proportional sampling with a total of 108 respondents. The respondents in this research were MSMEs in the Magelang Regency processing industry. Data collection techniques by providing offline and online questionnaires to respondents. The research results show that literacy and digitalization of MSMEs have a positive effect on the sustainability of MSMEs, while accounting skills have no effect on the sustainability of MSMEs. Financial literacy and digitalization make a positive contribution to the sustainability of MSMEs through increasing operational efficiency and market access.